2020
DOI: 10.3390/catal10020242
|View full text |Cite
|
Sign up to set email alerts
|

Dry Reforming of Methane Using Ce-modified Ni Supported on 8%PO4 + ZrO2 Catalysts

Abstract: Dry reforming of methane (DRM) was studied in the light of Ni supported on 8%PO 4 + ZrO 2 catalysts. Cerium was used to modify the Ni active metal. Different percentage loadings of Ce (1%, 1.5%, 2%, 2.5%, 3%, and 5%) were tested. The wet incipient impregnation method was used for the preparation of all catalysts. The catalysts were activated at 700 • C for 1 2 h. The reactions were performed at 800 • C using a gas hourly space velocity of 28,000 mL (h·gcat) −1 . X-ray diffraction (XRD), N 2 physisorption, hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…Noted, it was discovered that adding Ni as a dopant boosts the efficiency of zeolite in HDO and cracking [20]. Although many researchers have focused on the modification of zeolite catalysts in HDO and cracking reactions by the addition of various active metals such as noble metals (Pt, Pd, Ru) [21][22][23] and transition metals (Ni, Co, Mo) [5,[24][25][26], nevertheless, to the best of our knowledge, less study has focused on a detailed comparison of the effectiveness of HDO activity over pure zeolite beta and HZSM5 catalysts. Due to aforementioned finding, therefore, this study will highlight on the impact of zeolite beta and HZSM5 on the behavior and hydrocarbon selectivity of the oleic acid (OA) HDO reaction towards the diesel fraction.…”
Section: Introductionmentioning
confidence: 99%
“…Noted, it was discovered that adding Ni as a dopant boosts the efficiency of zeolite in HDO and cracking [20]. Although many researchers have focused on the modification of zeolite catalysts in HDO and cracking reactions by the addition of various active metals such as noble metals (Pt, Pd, Ru) [21][22][23] and transition metals (Ni, Co, Mo) [5,[24][25][26], nevertheless, to the best of our knowledge, less study has focused on a detailed comparison of the effectiveness of HDO activity over pure zeolite beta and HZSM5 catalysts. Due to aforementioned finding, therefore, this study will highlight on the impact of zeolite beta and HZSM5 on the behavior and hydrocarbon selectivity of the oleic acid (OA) HDO reaction towards the diesel fraction.…”
Section: Introductionmentioning
confidence: 99%
“…On adding phosphate, the charge transfer bands of ZrO 2 are demolished which indicates the perturbation of charge transfer due to the addition of phosphate in the support structure. The UV band of Phosphate‐ zirconia supported nickel catalyst (Ni/PZr) catalyst is found at 286 nm for charge transfer from O 2− to octahedral Ni +2 , about 423 nm for the d‐d transition from 3A 2 g(F) state to 3T 1 g(P) the state of Ni +2 in octahedral/distorted octahedral environment and about 730 nm shows the d‐d transition from 3A 2 g(F) state to 3T 1 g(F) state of the Ni +2 octahedral environment 46 . The Ce/PZr catalyst shows a UV band of about 280 nm for the transition of O 2− to Ce +3 /Ce +4.…”
Section: Resultsmentioning
confidence: 97%
“…Acido‐basic property of catalyst surface is a crucial factor to catalyze a reaction. Ibrahim et al found that ceria addition causes growth of basic site over the surface and at 3 wt% ceria, it has a moderate amount of weak acid site/surface hydroxyl 46 We have characterized catalyst sample with NH 3 ‐TPD to know the distribution of the acidic sites over the catalyst surface. With increasing ceria loading, the acidic character in the low‐temperature range/weak acidic character decreases, and at 10Ni3Ce/PZr catalyst, a moderate amount of weak basic sites are present.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations